Excavations at Tall Jawa, Jordan, Volume 1 The Iron Age Town - Daviau, Michèle, (Culture and History of the Ancient Near East ;, 2003)
Located in a strategic position on the southern flank of the Ammonite hill country, overlooking the Madaba Plain, the earliest settlement at Tall Jawa dates to the Iron I period (1100-900 BC). This settlement was redesigned during Iron Age II (900-600 BC), and consisted of a walled town, surrounded by a casemate style fortification system and a multi-chambered gate complex. Major buildings, standing to the second storey, are described in detail with their furnishings and contents. A marked change in architecture, ceramic technology, and high status artefacts mark the high point of Tall Jawa during the period of the Assyrian empire (730-600 BC). The major features of each structure are illustrated both in the text and on a CD-ROM. This volume presents the final report of six seasons of excavations at Tall Jawa in central Jordan. The particular focus of this report is the architecture and stratigraphy of the settlements which occupied the site during the Iron Age (1100-600 BC).